2009
DOI: 10.1016/j.jneumeth.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for precisely timed stimulation of mouse whiskers in a freely moving preparation: Application for delivery of the conditioned stimulus in trace eyeblink conditioning

Abstract: The somatosensory whisker pathway has been a useful system for increasing our understanding of experience-induced plasticity. However, precisely timed whisker activation in the awake freely moving mouse has been very difficult. This manuscript describes a method for construction of a whisker stimulator that can be attached to a freely moving mouse. The stimulator was used to activate the whiskers in a time-sensitive forebrain-dependent task, trace eyeblink conditioning. After repeatedly pairing whisker stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Each mouse was lightly anesthetized with isoflorane and all the whiskers except the C row on both hemispheres were trimmed to 0.5cm (the whisker stimulator sits approximately 1cm from the face (Galvez et al, 2008)) 24 hours prior to conditioning. Mouse whiskers grow approximately 1mm / day (Ibrahim and Wright, 1975, 1983).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each mouse was lightly anesthetized with isoflorane and all the whiskers except the C row on both hemispheres were trimmed to 0.5cm (the whisker stimulator sits approximately 1cm from the face (Galvez et al, 2008)) 24 hours prior to conditioning. Mouse whiskers grow approximately 1mm / day (Ibrahim and Wright, 1975, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were habituated to the training chamber 24 hours later. The mice were then WCS trained for 4 days on either a trace- or pseudo-eyeblink paradigm (Fig.1) (Galvez et al, 2008). This was then followed by ACS training for 4 days on a trace- or pseudo-eyeblink paradigm with an additional 2 days on a delay- or pseudo-eyeblink paradigm (Fig.1).…”
Section: Methodsmentioning
confidence: 99%
“…The barrel cortex receives somatosensory information from facial whiskers, and therefore it has been used to study cortical plasticity during fear conditioning in which whisker stimulation is paired with a footshock 27 . Whisker stimulation has also been used for a whisker-signalled trace eyeblink-conditioning task; in this case, repeatedly pairing whisker stimulation with a mild periorbital shock 28 (or air puff 29 ; see below), following a stimulus-free trace interval, triggered trace conditioning in mice. These results were extended by recent work using two-photon in vivo calcium imaging that showed that pairing whisker stimulation with a footshock led to a decrease in the number of neurons in the barrel cortex that responded to whisker stimulation 29 , suggesting refinement of the memory trace.…”
Section: Neuronal Allocationmentioning
confidence: 99%
“…Mice were trained one session per day for eleven days. Each session had 30 trials with a mean inter-trial interval (ITI) of 45-s ±15-s. Mice received two paired stimuli: a conditioned stimulus (CS), a deflection of the whiskers on one side of the muzzle driven by a piezo actuator attached to the tether (60 Hz, 250 μm deflection) and an unconditioned stimulus (US), a periorbital shock sufficient to cause reliable eyeblinks (0.25–2 mA train of biphasic square wave shocks, 60 Hz, 0.5 ms pulses) (Galvez, Weiss, Cua, & Disterhoft, 2009). Training consisted of one day of habituation to the eyeblink chamber (no CS/US), followed by five days of training (paired CS/US) and five days of extinction (CS alone).…”
Section: Methodsmentioning
confidence: 99%